9514 1404 393
Answer:
D. 28 +10i
Step-by-step explanation:
As with any "collect terms" problem, you first identify the like terms, then add their coefficients. You can start with either the real or the imaginary terms to obtain a result that will point you to the correct answer choice. Of course, the distributive property works in the usual way.
(3i+ 4) -i + 4(6 +2i) = 3i +4 -i +24 +8i . . . . eliminate parentheses
= (4 +24) +(3 -1 +8)i . . . . . . . group like terms
= 28 +10i
Answer:
great
Step-by-step explanation:
Answer:
(- 4, 1 )
Step-by-step explanation:
Given the 2 equations
y = x + 5 → (1)
x - 5y = - 9 → (2)
Substitute y = x + 5 into (2)
x - 5(x + 5) = - 9 ← distribute and simplify left side
x - 5x - 25 = - 9
- 4x - 25 = - 9 ( add 25 to both sides )
- 4x = 16 ( divide both sides by - 4 )
x = - 4
Substitute x = - 4 into either of the 2 equations and evaluate for y
Substituting into (1)
y = - 4 + 5 = 1
Solution is (- 4, 1 )
Answer:
7/5 * A *y =k
Step-by-step explanation:
A=5k/7y
Multiply each side by 7y
A* 7y = 5k/7y * 7y
7Ay = 5k
Divide by 5
7Ay/5 = 5k/5
7/5 * A *y =k